Analisis Bahasa Persuasif Pemicu Fomo (Fear of Missing Out) dalam Promosi UMKM (Konteks Pasar Persaingan Sempurna) di Pasar Sentral Gorontalo - Agustin, Puspita Dian; Bauna, Afra Amatullah; Adam, Alisya; Rauf, Apriyana Abd; Aprilia, Damayanti; Ntuu, Mahmud A.; Ruqyah, Miss; ‘Abid, Muhammad; Ilham, Muhammad; Malureng, Nirfa Celia; Paimin, Randy Octaviano Hermanus; Molantong, Salsabila Lutfiah; Monoarfa, Yuniar Sari (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Language plays a strategic role in economic activities particularly in promotion and marketing, through persuasive language that influences consumer interest and decisions. This study aims to analyze the use of persuasive triggering Fear of Missing Out (FOMO) in the promotion of newly opened Micro, Small, and Medium Enterprises (MSMEs). The research employs a descriptive method with a qualitative approach using observation, semi-structured interviews, and documentation, with informants selected through purposive sampling. Results indicate that persuasive language appears in direct invitations, simple information, and utterances emphasizing urgency dan scarcity, FOMO is a psychological response influenced by social factors rather than a deliberate strategy. This study suggests that persuasive language functions as a non-price promotional straregy.